2014
DOI: 10.1002/jcp.24512
|View full text |Cite
|
Sign up to set email alerts
|

Osteoactivin Induces Transdifferentiation of C2C12 Myoblasts Into Osteoblasts

Abstract: Osteoactivin (OA) is a novel osteogenic factor important for osteoblast differentiation and function. Previous studies showed that OA stimulates matrix mineralization and transcription of osteoblast specific genes required for differentiation. OA plays a role in wound healing and its expression was shown to increase in post fracture calluses. OA expression was reported in muscle as OA is upregulated in cases of denervation and unloading stress. The regulatory mechanisms of OA in muscle and bone have not yet be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…These observations confirm our previous published findings that OA/gpnmb over‐expression in osteoblasts in vitro stimulated their differentiation (Abdelmagid et al, ). We have also shown that OA increases osteoblast markers and decreases myoblast markers in vitro (Sondag et al, ). These data combined suggest that OA/gpnmb promotes osteoprogenitor differentiation primarily through up‐regulation of osteoblast differentiation markers.…”
Section: Discussionmentioning
confidence: 70%
“…These observations confirm our previous published findings that OA/gpnmb over‐expression in osteoblasts in vitro stimulated their differentiation (Abdelmagid et al, ). We have also shown that OA increases osteoblast markers and decreases myoblast markers in vitro (Sondag et al, ). These data combined suggest that OA/gpnmb promotes osteoprogenitor differentiation primarily through up‐regulation of osteoblast differentiation markers.…”
Section: Discussionmentioning
confidence: 70%
“…52 Previous studies have shown that the presence of specific factors can stimulate transdifferentiation of C2C12 myoblasts into osteoblasts. [53][54][55] The osteogenic capability of bECM hydrogels was measured in vitro with the myoblastic C2C12 cell line, by co-incubation of bECM and type I collagen with C2C12 cells with low and rich serum mediums. Differentiation was assessed by expression of ALP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the involvement of BMP9 in the pathogenesis of heterotopic ossification was demonstrated (Kaji, 2014). Recently, a parathormone responsive local factor, Tmem119 as well as oeteoactivin were found to promote and induce the differentiation of myoblasts into osteoblasts (Tanaka et al, 2012;Kaji, 2014;Sondag et al, 2014).…”
Section: Ectopic Bone Formation In Skeletal Musclementioning
confidence: 98%